Enhanced CO 2 /CH 4 Permselectivity in Partially Hydrolyzed EVA Membranes via Synergistic PEG Plasticization and Amine-Functionalized Silica Incorporation - Chonlada Ritvirulh; Patchnakan Wisatsuvan; Tawan Sooknoi; Suparat Rukchonlatee (ACS Applied Polymer Materials, 2026)
The separation of carbon dioxide (CO2) from methane (CH4) in biogas is essential for increasing the fuel quality. However, conventional membrane-based separation under high pressure is not suitable for household biogas systems due to operational cost and complexity. This study aims to develop low-pressure gas separation membranes based on partially hydrolyzed ethylene vinyl acetate (p-E) copolymers by incorporating poly(ethylene glycol) (PEG) as a plasticizer and amine-functionalized silica (APTES-modified SiO2) as a polar filler. The hydrolysis of EVA improves mechanical strength by increasing hydrogen bonding. PEG addition enhances the free volume and CO2 affinity, while the well-dispersed surface-treated SiO2 increases membrane polarity and suppresses CH4 permeation. Among the tested membranes, the optimal formulation (p-EP400(15)-S0.6) containing 15 wt % PEG400 and 0.6 wt % APTES-SiO2 achieves the highest CO2/CH4 selectivity (∼22) and a high CO2 permeability (∼1400 g/m2·day). These findings demonstrate a promising strategy to develop effective membranes for biogas upgrading under ambient conditions.
Keywords: Membrane Separation and Gas Transport; Carbon Dioxide Capture Technologies; Membrane Separation Technologies